Effect of acupoint application combined with acupoint massage on constipation of liver-qi stagnation after replantation of severed fingers (穴位贴敷联合按摩在断指再植术后肝郁气滞型便秘患者中的应用效果研究) - TIAN Miaomiao (田苗苗); XIAO Junyan (肖俊艳) (Association of Integrative Nursing, 2023)
Objective To observe the effect of acupoint application combined with acupoint massage on constipation of liver-qi stagnation after replantation of severed fingers. Methods Totally 60 patients with constipation of liver-qi stagnation after finger replantation were randomly divided into study group and control group, with 30 patients in each group. Based on routine nursing after hand-foot surgery, patients of both groups were given medication for defecation according to the doctor's advice. In the experimental group, patients were treated with 15 minutes of acupoint massage combined with Shenque acupoint external application. From the day after surgery, the defecation condition was evaluated by Cleveland Clinic Constipation Score (CSS) and Bristol Stool Form Scale(BSFS) in both groups. Negative emotions of patients were measured by Self-rating Anxiety Scale(SAS) and Self-rating Depression Scale (SDS) before intervention, on the day after surgery, one week after surgery and two weeks after surgery respectively. Results The CSS score in the study group was lower than that in the control group after intervention(P＜0. 05). The BSFS score in the study group was higher than that in the control group after intervention(P＜0. 05). The SAS score and SDS scores were decreased in both groups after intervention, and SAS score and SDS scores in the study group were lower than that in the control group after intervention(P＜0. 01). The overall effective rate was 96. 67%(29/30)in the study group, which was higher than 83. 33%(25/30) in the control group (P＜0. 05). Conclusion Acupoint application combined with massage has a significant effect on liver-qi stagnation constipation after finger replantation, which can effectively improve the constipation symptoms and relieve patients' negative emotion such as anxiety and depression. (目的 观察穴位贴敷联合按摩对断指再植术后肝郁气滞型便秘的干预效果。方法 60例断指再植术后肝郁气滞型便秘患者随机分为研究组和对照组, 各30例。对照组给予手足外科常规治疗及护理, 对术后便秘患者遵医嘱给予药物通便; 研究组在对照组基础上, 对术后便秘患者给予15 min穴位按摩联合神阙穴穴位贴敷干预。术后当天开始进行便秘临床症状评分(CCS)和Bristol粪便性状评分(BSFS); 采用焦虑自评量表(SAS)和抑郁自评量表(SDS)对评估两组患者情绪状态; 根据中医证候积分改善情况评价疗效。结果 干预后, 研究组CCS评分低于对照组, 差异有统计学意义(P＜0. 05)。干预后, 研究组BSFS评分高于对照组, 差异有统计学意义(P＜0. 01)。干预后, 两组SAS和SDS评分均较干预前下降, 且研究组SAS和SDS评分低于对照组, 差异有统计学意义(P＜0. 01)。研究组总有效率96. 67%(29/30), 高于对照组的83. 33%(25/30), 差异有统计学意义(P＜0. 05)。结论 穴位贴敷联合按摩干预断指再植术后肝郁气滞型便秘效果明确, 可有效改善患者便秘症状, 缓解患者焦虑、抑郁等负性情绪。)